Initial results from boron powder injection experiments in WEST lower single null L-mode plasmas. (1st August 2022) - Bodner, G.; Gallo, A.; Diallo, A.; Lunsford, R.; Moreau, Ph.; Nagy, A.; Pellissier, F.-P.; Guillemaut, C.; Gunn, J.P.; Bourdelle, C.; Desgranges, C.; Manas, P.; et al.
Abstract: Using a recently installed impurity powder dropper (IPD), boron powder (<150 μ m) was injected into lower single null (LSN) L-mode discharges in WEST. IPDs possibly enable real-time wall conditioning of the plasma-facing components and may help to facilitate H-mode access in the full-tungsten environment of WEST. The discharges in this experiment featured I p = 0.5 MA, B T = 3.7 T, q 95 = 4.3, t pulse = 12–30 s, n e, 0 ∼ 4 × 10 19 m −2, and P LHCD ∼ 4.5 MW. Estimates of the deuterium and impurity particle fluxes, derived from a combination of visible spectroscopy measurements and their corresponding S/XB coefficients, showed decreases of ∼50% in O +, N +, and C + populations during powder injection and a moderate reduction of these low- Z impurities (∼50%) and W (∼10%) in the discharges that followed powder injection. Along with the improved wall conditions, WEST discharges with B powder injection observed improved confinement, as the stored energy W MHD, neutron rate, and electron temperature T e increased significantly (10%–25% for W MHD and 60%–200% for the neutron rate) at constant input power. These increases in confinement scale up with the powder drop rate and are likely due to the suppression of ion temperature gradient (ITG) turbulence from changes in Z eff and/or modifications to the electron density profile.